The Black Box of Governmental Learning : The Learning Spiral - A Concept to Organize Learning in Governments - Blindenbacher, Raoul; Nashat, Bidjan (World Bank, 2012)
There are more poor people and poverty reaches further into middle-income countries around the world than ever before. Adequate governmental capacity development is considered one of the critical missing factors in current efforts to reduce poverty and, by doing so, to meet the millennium development goals. If the development of sustainable capacity is not given greater attention in the near future, development efforts in the poorest countries are expected to fail even if they are supported with substantially increased funding. One effective way to improve the quality of democratic governments is by their learning from the past and from each other's experiences. But to what extent are governments capable of and/or willing to learn? And if they are, what are they supposed to learn-and how? Is the way they learn different from the way individuals or organizations learn? Under what conditions do they learn best, and to what extent can learning events enhance their capacities to improve the performance of their public sectors? These and many related questions are examined in the black box of governmental learning.